Expanding the environmental virome: Infection profile in a native rainforest tree species - Vieira, Anderson Carvalho; Lopes, Ícaro Santos; Fonseca, Paula Luize Camargos; Olmo, Roenick Proveti; Bittencourt, Flora; de Vasconcelos, Letícia Maróstica; Pirovani, Carlos Priminho; Gaiotto, Fernanda Amato; Aguiar, Eric Roberto Guimarães Rocha (Frontiers in Microbiology, 2022)
Agroforestry systems (AFS) for cocoa production combine traditional land-use practices with local biodiversity conservation, resulting in both ecological and agricultural benefits. The cacao-cabruca AFS model is widely implemented in regions of the Brazilian Atlantic Forest. Carpotroche brasiliensis (Raddi) A. Gray (Achariaceae) is a tree found in cabruca landscapes often used for reforestation and biotechnological applications. Despite its importance, we still lack information about viruses circulating in C. brasiliensis, especially considering the possibility of spillover that could affect cocoa production. In our study, we analyzed the Carpotroche brasiliensis virome from Atlantic Forest and cacao-cabruca AFS regions using metatranscriptomics from several vegetative and reproductive organs. Our results revealed a diverse virome detecting near-complete single- and double-stranded DNA and RNA viruses classified into at least six families (Botourmiaviridae, Bromoviridae, Caulimoviridae, Genomoviridae, Mitoviridae, and Rhabdoviridae) plus unclassified elements. We described with high confidence near-complete genomes of two tentative novel viruses (Carpotroche-associated ilarvirus and Carpotroche-associated genomovirus). Interestingly, we also described sequences likely derived from a rhabdovirus, which could represent a novel member of the genus Gammanucleorhabdovirus. We observed higher viral diversity in cacao-cabruca AFS and in reproductive organs of C. brasiliensis with preferential tropism to fruits, which could directly affect production. Altogether, our results provide data to better understand the virome in this unexplored agroecological interface, such as cacao-cabruca AFS and forest ecosystem, providing information on aspects of virus-plant interactions.